Echoing in Memory: Musicalization as an Effective Strategy for Enjoyable Hadith Memorizing - Khofifah Diana Pangestuti; Muhammad Misbah; Muhammad Miftah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Memorizing hadith is often considered a difficult and boring activity by most students, especially those unfamiliar with traditional approaches that are generally monotonous and repetitive. This study offers an innovative solution to increase the effectiveness and interest of students in memorizing hadith. The main focus of the study is to design a musicalization strategy as a tool for enjoyable hadith memorization. The purpose of this study was to explore the use of musicalization as an innovative strategy in the process of memorizing hadith. This study used a qualitative approach with literature review methods, as well as analysis of educational theory and music psychology. The results showed that the use of musicalization as a strategy in memorizing hadith has a significant positive impact on improving memory and enhancing the learning atmosphere. Musicalization, which combines elements of melody, rhythm, and lyrics, stimulates the right and left brain simultaneously, creating optimal cognitive synergy. The repetitive melodic and rhythmic patterns help students recall hadith texts more easily, while the emotional associations created through music strengthen long-term information retention.